What has affected the governance effect of the whole population coverage of medical insurance in China in the past decade? Lessons for other countries - Zhang, Ting; Zhang, Hongyu; Miao, Wenqing; Xu, Jinpeng; Shi, Qi; Liu, Jian; Deng, Fangmin; He, Jingran; Chen, Fangting; Kang, Zheng; Wu, Qunhong; Tian, Guomei (Frontiers in Public Health, 2023)
Objective: This paper aims to explore the current state of governance of full population coverage of health insurance in China and its influencing factors to provide empirical references for countries with similar social backgrounds to China. Methods: A cross-sectional quantitative study was conducted nationwide from January 22-26, 2020, with descriptive statistics, analysis of variance, and logistic regression models via SPSS 25.0 to analyze the effectiveness and influencing factors of the governance of full population coverage of health insurance in China. Results: 59% of the survey respondents rated the effectiveness of health insurance total population coverage governance as good. According to the statistical results, the ability of the population to participate in the insurance, the degree of information construction of the health insurance department, and the power of governance and governance tools have a significant effect on the effectiveness of the governance of health insurance total population coverage (P<0.05). Conclusions: Chinese health insurance full population coverage governance is effective. To effectively improve the effectiveness of health insurance total population coverage governance, health insurance information construction, governance capacity, and governance tools should be the focus of governance further to enhance the expansion and increase of health insurance coverage.